Pengaruh Diskon Flash Sale, Rating Dan Gratis Ongkos Kirim Terhadap Keputusan Pembelian Pada Marketplace Shopee - Miftakhul Jannah; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The growth of the e-commerce business that is getting bigger and faster in Indonesia has caused many other e-commerce to appear and offer various advantages and conveniences as well as lead to increasingly fierce competition between major e-commerce companies in Indonesia in fighting for first place in various aspects. The purpose of this study was to determine the effect of Flash Sale Discounts, Ratings and Free Shipping on purchasing decisions on the Shopee Marketplace. This type of research is quantitative with multiple linear regression data analysis. The results showed that Flash Sale Discounts, Ratings, Free Shipping had a significant effect on Shopee Marketplace Purchase Decisions, Flash Sale Discounts had a significant positive effect on Purchase Decisions, Ratings had a significant negative effect on Purchase Decisions and Free Shipping had a significant negative effect on Purchase Decisions. Keywords: Flash Sale Discount, Rating, Free Shipping, Buying Decision